Designing unlocked gramm application to promote students’ self-directed learning - Indrayani, Ninuk; Khumaidah, Sofkhatin (JEES (Journal of English Educators Society), 2023)
The process of self-direction is viewed as essential for achieving worthwhile and significant educational achievements. It is related to setting up learning objectives, keeping one's intentions, and aiming for high-quality learning. In order for students to reach the ultimate educational goal of being continuous learners with the ability for future educational progress, learning interests, and possibilities for lifelong learning, self-direction with the involvement of technology is considered as crucial. The objective of this study was to create the Unlocked Gramm mobile application, which would increase students’ motivation to learn grammar and promote students' self-directed learning using Design and Development (D&D) methodology as research design. Questionnaire with quantitative analysis and interview for qualitative analysis were used to examine the design, development, and evaluation of the media. The study was considered successful with the score of Likert Scale 3.8 from the range 1-5 to the fact that the generated application was a good medium and satisfied the requirements for an appropriate media based on the evaluation results. Using Unlocked Gramm can be challenging and a solution for both teachers and students to keep themselves interested in and motivated to actively learning grammar. The main goal is to encourage self-directed learning as a crucial element of adult education, which leads to the students' successful learning. It is imperative to put self-directed learning into practice, particularly in formal educational settings like higher education institutions. HIGHLIGHTS: Technology and self-directedness support lifelong learning Unlocked Gramm touches the interest of digital native in learning Grammar A fun Grammar learning can be done at anywhere and anytime with Unlocked Gramm